Antioxidant Properties and Storage Behavior of Malayan Cherry Fruit Water Extracts - Hamad, Alwani; Santika, Dita; Hartanti, Dwi (Universitas Muhammadiyah Yogyakarta, 2026)
The fruits of the Malayan cherry (Muntingia calabura L.) have been used for diabetes management in Banyumas due to their potential antioxidant properties. This study aims to optimize water extraction for antioxidant properties and determine the organoleptic and physicochemical properties of the selected extracts during 18 days of storage. The effects of the extraction method (infusion, 15-min decoction, 30-min decoction) and the drug-to-solvent ratio (1:10, 1:20, 1:100) on total flavonoid content (TFC), total phenolic content (TPC), and antioxidant activity, measured by DPPH scavenging activity and FRAP methods, were evaluated using their respective standard assays. The selected extract (from infusion at a 1:20 ratio) was stored in airtight bottles at 4±2 °C for 18 days. The organoleptic, pH, and antioxidant properties stability was evaluated accordingly. The crude drug-to-solvent ratio significantly affected TFC, with the 1:100 ratio generating the highest value (6.43 mg QE/g DW). Both the extraction method and the solvent ratio significantly defined TPC, DPPH scavenging activity, and FRAP, with the infusion at a 1:20 ratio showing the highest TPC (4.15 mg GAE/g DW), DPPH scavenging activity (25.2 mmol TE/100 g DW), and FRAP (93.93 mmol TE/100 g DW). Infusion at a 1:20 ratio showed significant decreases in pH, TFC, TPC, and DPPH scavenging activity on day 6 of storage, whereas changes in aroma and taste were observed on day 12. The infusion method at a 1:20 ratio is optimal for extracting antioxidants from Malayan cherry fruit extract. However, its application is limited by significant bioactive degradation during storage, which needs to be addressed with the development of a suitable dosage form.